A rare incidental encounter of unilateral choanal atresia during adenotonsillectomy in a 5-year-old child: A case report from Tanzania - Abraham, Zephania Saitabau; Massawe, Enica Richard; Mapondella, Kassim Babu; Kahinga, Aveline Aloyce; Ntunaguzi, Daudi (Indian Journal of Case Reports, 2020)
Unilateral choanal atresia refers to a congenital anomaly whereby a child is born with unilateral imperforate posterior nare. In most cases, the diagnosis is established several years after birth. The establishment of the diagnosis requires a high index of suspicion by clinicians. We report an unusual case of a 5-year-old girl who was diagnosed intraoperatively to have unilateral choanal atresia (right) during elective adenotonsillectomy after the failure of introducing a nasal catheter into the oropharynx and on digital palpation of the choanae intraorally. Endoscopic perforation of the membranous atretic choanal plate was done in the same sitting with adenotonsillectomy. The objective of this case report was thus to report an unusual case which went undiagnosed for 5 years and was diagnosed intraoperatively during elective adenotonsillectomy and also to review the few available pieces of the literature. To the best of our knowledge, this is so far the second reported case worldwide of unilateral choanal atresia incidentally diagnosed during adenotonsillectomy.